Analysis of Personal Financial Management, Financial Literacy, and Digital Finance in Generation Z in Supporting Sustainable Consumption - Monica Dewi; Agung Dharmawan Buchdadi; Wahyu Wastuti (Journal of Business and Behavioural Entrepreneurship, 2025)
This study examines the influence of personal financial management, financial literacy, and digital finance on sustainable consumption among Generation Z in Indonesia. Using a quantitative approach with purposive and convenience sampling, data were collected from 40 respondents aged 18–23 with a minimum monthly income of IDR 5,000,000. The results, analyzed using SEM-PLS, indicate that all three variables personal financial management, financial literacy, and digital finance significantly impact sustainable consumption. The findings highlight the importance of financial literacy and digital tools in promoting environmentally and socially responsible consumption behaviors. This research contributes to the literature by integrating financial literacy, digital finance, and environmental awareness into a sustainable financial decision-making model for Generation Z, offering practical implications for policymakers and educators aiming to foster sustainable consumption practices.